Microemulsions Loaded with Plinia cauliflora Extract and Fractions for Topical Application Against Cutaneous Mycosis - Rodrigo Sorrechia; Camila Cristina Baccetti Medeiros; João Vitor Carvalho Constantini; Rafaela Regina Fantatto; Bárbara Regina Kapp; Nathália Ferreira Fregonezi; Ana Melero; Ana Marisa Fusco-Almeida; Marlus Chorilli; Rosemeire Cristina Linhari Rodrigues Pietro (Cosmetics)
Fungal infections, including skin ones, due to resistant strains combined with the gap in discovering new antifungal compounds have presented great medical importance; thus, we evaluated the antifungal properties of Plinia cauliflora, a Brazilian plant known as jabuticabeira, as its fruits have been used in traditional medicine, which has been scientifically proved. The differential in this study was the use of leaves to obtain the ethanolic extract and its fractions and with incorporation in microemulsions that can increase the activity, promoting greater availability of active components in therapeutic targets. Candida glabrata has been very prominent in nosocomial infections and our results were very promising, showing a minimum inhibitory concentration of 4.88 μg/mL for the extract and about a 4-fold decrease with its microemulsion reaching 1.22 μg/mL; for the dermatophytic fungus Trichophyton rubrum, this decreased 2-fold, from 156.25 μg/mL to 78.12 μg/mL. The antioxidant activity was also studied, showing the best results for the extract at 25.6 μg/mL and lastly, the samples were not toxic when the Galleria mellonella model was used. Thus, the results demonstrate the activity of the extract, and that the incorporation was able to increase the antifungal activity in a safe, non-toxic manner, making it possible to provide a therapeutic option for these fluconazole-resistant microorganisms.